THE INFLUENCE OF DIGITAL CULTURE AND LEADERSHIP STYLE ON EMPLOYEE PERFORMANCE WITH WORK MOTIVATION AS A MEDIATION VARIABLE AT FINNS BALI - Dian Mariany; Adrie Frans Assa (CV. Radja Publika, 2026)
Abstract — Digital transformation has encouraged organizations to establish a strong digital culture and implement effective leadership practices to improve employee performance. However, the success of these initiatives is often influenced by employees' work motivation. This study aims to examine the effects of digital culture and leadership style on employee performance, with work motivation serving as a mediating variable at FINNS Bali. A quantitative approach was employed using a survey method involving employees of FINNS Bali. The data were analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM). The findings indicate that digital culture has a positive and significant effect on work motivation but does not directly influence employee performance. Leadership style positively and significantly influences both work motivation and employee performance. Furthermore, work motivation has a positive and significant effect on employee performance and mediates the relationship between digital culture and employee performance, as well as the relationship between leadership style and employee performance. These findings highlight the importance of strengthening work motivation through the implementation of digital culture and effective leadership practices to enhance employee performance within the hospitality industry.